A study of the challenges faced by the visually impaired students at Midlands State University, in Gweru, urban district, Zimbabwe - Fillipus, Aina (Midlands State University, 2017)
The purpose of this study was to find out if visually impaired students at Midlands State University are facing similar challenges as students in Namibia at Secondary schools in their learning environments. The researcher intended to find solutions to the problems that are faced by the visually impaired students at Midlands State University. The research employed qualitative and quantitative data collection procedures through the use of triangulation ofinstruments: the observation, interviews and questionnaires. The research targeted the population of twenty 20 participants in the university .The sample consisted of, four4visually impaired students,six 6 workers at the DRC and ten 10lecturers teaching visually impaired students. The population of visually impaired students and workers at the DRC are in small numbers hence the researcher intended to use the whole group as a sample and use purposive sampling for the lecturers teaching visually impaired students. The research was guided by the descriptive survey design.100% of thesample participated in the study, and responded to the research questions provided. The evidencepointed to the fact that the disabled students (VIS) at Midlands State University are the mostdisadvantaged students with numerous challenges which contributed to their academic performance. The findings also suggested that the University’s infrastructure was blindly built without thinking about the disabled students’ safety and accessibility issues. The researcher also concluded that since there are inadequate learning human, capitals,and material resources such as specialist instructors and sport trainers, textbooks, Braille and Perkins machines, large printers, CCTV, and the lack of proper sport facilities for the VIS were also sadly missing. It is recommended that the University should offer short courses or in-service training on how to make the classrooms for inclusive classes cater for the special needs education particularly to lecturers who should be educated, through adaptations of teaching and learning environments.